Electrical Stimulation Frequency and Skeletal Muscle Characteristics: Effects on Force and Fatigue - Maria Vromans; Pouran Faghri (PAGEPress Publications, 2017)
This investigation aimed to determine the force and muscle surface electromyography (EMG) responses to different frequencies of electrical stimulation (ES) in two groups of muscles with different size and fiber composition (fast- and slow-twitch fiber proportions) during a fatigue-inducing protocol. Progression towards fatigue was evaluated in the abductor pollicis brevis (APB) and vastus lateralis (VL) when activated by ES at three frequencies (10, 35, and 50Hz). Ten healthy adults (mean age: 23.2 ± 3.0 years) were recruited; participants signed an IRB approved consent form prior to participation. Protocols were developed to 1) identify initial ES current intensity required to generate the 25% maximal voluntary contraction (MVC) at each ES frequency and 2) evaluate changes in force and EMG activity during ES-induced contraction at each frequency while progressing towards fatigue. For both muscles, stimulation at 10Hz required higher current intensity of ES to generate the initial force. There was a significant decline in force in response to ES-induced fatigue for all frequencies and for both muscles (p<0.05). However, the EMG response was not consistent between muscles. During the progression towards fatigue, the APB displayed an initial drop in force followed by an increase in EMG activity and the VL displayed a decrease in EMG activity for all frequencies. Overall, it appeared that there were some significant interactions between muscle size and fiber composition during progression towards fatigue for different ES frequencies. It could be postulated that muscle characteristics (size and fiber composition) should be considered when evaluating progression towards fatigue as EMG and force responses are not consistent between muscles.